Factors Affecting Iron Deficiency Anemia in Young Women in the Working Area of the Puuwatu Health Center - Amalia, Risqi; Ismayanti (Arus Jurnal Sains dan Teknologi, 2025)
Anaemia is a deficiency of macronutrients (protein) and micronutrients, especially iron. Anaemia is mostly experienced by adolescent girls due to experiencing menstrual cycle nutritional imbalances, which can have a long impact on themselves and their future children. The impact of anaemia is the disruption of growth and development, increased susceptibility to infection due to a decreased immune system, to be more susceptible to poisoning. haemoglobin levels in the blood are less than the normal amount The prevalence rate of anaemia in adolescents aged 15-24 years is 32%. According to WHO, the normal haemoglobin level for women over 15 years old is >12.0 g/dl (>7.5 mmol). Anaemia has a negative impact on the health of an adolescent if it occurs continuously. This study aims to determine the factors that influence the incidence of anaemia in adolescent girls such as poor diet, poor sleep patterns and lack of physical activity in junior and senior high school students in the working area of Puskesmas PuuwatuKendari City in 2024. The research method used was the provision of health education related to anaemia through printed leaflets, lecture and discussion methods. The information presented included guidance and knowledge about anaemia and the provision of FE tablets for adolescent girls in an effort to prevent anaemia. With a population of 1450 adolescent girls and a sample of 314 adolescent girls. According to data from Puskesmas Puuwatu in 2024, there were 9 cases of severe anaemia and 69 cases of moderate anaemia. After intervening with adolescent girls by providing knowledge about good diet, good sleep patterns and doing physical activity, it was found that there was a decrease in anaemia cases to 49 people. So it is still necessary to intervene in depth and more by conducting counseling to adolescent girls so that in the future anaemia cases can be suppressed properly